EFEKTIVITAS PENYALURAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SD - Lilis Mulyatul Halimah; Heri Yusuf Muslihin; Fahmi Qodrul Asphar; Nunung Nurjanah; Susi Widianingsih (Universitas Muhammadiyah Surakarta, 2023)
This study aims to idescribe thei effectiveness of the distribution of school operational iassistance funds (BOS) in elementary schools in planning, implementing, monitoring, evaluating and reporting and accountability for the management of BOS fundsi in SDN Paganjuran, Cineam District, Tasikmalaya Regency.This research was conducted at SDN Paganjuran, Cineam District, Tasikmalaya Regency. Data were collected by observation, interview and documentation methods, which were then analyzed using a qualitative approach and descriptive analysis. The problem faced by all these elementary schools was that the School Operational Assistance (BOS) funds did not arrive on time as expected.The results showed that the BOS treasurer prepared the ARKAS ion time, namely ati the beginningi of th fiscal year, basedi on the priority scale of school needs, and involved icommittees andi teachers.The conclusion in this study is that the implementation aspect has not been entirely successful because the distribution of School Operational Assistance funds is still late. The aspect of supervision is still not fully successful because there is no supervision from the relevant agencies on a regular basis. Evaluationi activitiesi by the committee have been carried out although not optimal. Reporting on the management of BOS fund at SDN Paganjuran can be said to have been successful because a report has been made in accordance with the itechnical guidelines for managingi BOS funds. The level of effectiveness in managing BOS funds at SDN Paganjuran is in the effective criteria.Keywords: Management, Financing, Planning, Implementation, Evaluation.